Assessing the relevance and implementation of patient-centredness from the patients’ perspective in Germany: results of a Delphi study - Isabelle Scholl; Martin Härter; Stefan Zeh; Eva Christalle; Pola Hahlweg (BMJ Open)
Objective Patient-centredness (PC) has particularly grown in relevance in health services research as well as in politics and there has been much research on its conceptualisation. However, conceptual work neglected the patients’ perspective. Thus, it remains unclear which dimensions of PC matter most to patients. This study aims to assess relevance and current degree of implementation of PC from the perspective of chronically ill patients in Germany.Methods We conducted a Delphi study. Patients were recruited throughout Germany using community-based strategies (eg, newspapers and support groups). In round 1, patients rated relevance and implementation of 15 dimensions of PC anonymously. In round 2, patients received results of round 1 and were asked to re-rate their own results. Participants had to have at least one of the following chronic diseases: cancer, cardiovascular disease, mental disorder or musculoskeletal disorder. Furthermore, patients had to be at least 18 years old and had to give informed consent prior to participation.Results 226 patients participated in round 1, and 214 patients in round 2. In both rounds, all 15 dimensions were rated highly relevant, but currently insufficiently implemented. Most relevant dimensions included ‘patient safety’, ‘access to care’ and ‘patient information’. Due to small sizes of subsamples between chronic disease groups, differences could not be computed. For the other subgroups (eg, single disease vs multi-morbidity), there were no major differences.Conclusion This is one of the first studies assessing PC from patients’ perspective in Germany. We showed that patients consider every dimension of PC relevant, but currently not well implemented. Our results can be used to foster PC healthcare delivery and to develop patient-reported experience measures to assess PC of healthcare in Germany.